Understanding the lived experience of a Sioux Indian male adolescent: toward the pedagogy of hermeneutical phenomenology in education - Kim, Jeong-Hee (My University, 2012)
Currently, there is a resurgence of interests in phenomenology in education. This article sheds light on the importance of hermeneutical phenomenology in teaching and learning based on the lived experience of a Sioux Indian adolescent boy, elicited from an ethnographic case study conducted at an alternative high school in the US.Employing narrative inquiry, this article seeks phenomenological ways of understanding students’ lived experiences and explores the meaning of the pedagogical practice of hermeneutical phenomenology in education. I delve into how hermeneutical understanding of the phenomena of students’ lived experience can catapult both students and teachers into the personal growth and development in a reciprocal way. It is my hope that such an understanding will facilitate an educational aim that focuses on the ontology of being and becoming while students’ existence is brought to the center of teaching and learning.
Keywords: Sioux Indian; Hermeneutical phenomenology; Lived experience; Phenomenology; Pedagogy